Ribosomal Mutations in Arcanobacterium pyogenes Confer a Unique Spectrum of Macrolide Resistance - Jost, B. Helen (American Society for Microbiology, 2004)
Four macrolide-resistant Arcanobacterium pyogenes isolates contained A2058T, A2058G, or C2611G (Escherichia coli numbering) mutations in their 23S rRNA genes. While these mutations conferred resistance to erythromycin, oleandomycin, and spiramycin, they did not confer resistance to tylosin.